2009
DOI: 10.14411/eje.2009.077
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of a relict population of the vulnerable butterfly Pyrgus sidae on the Iberian Peninsula (Lepidoptera: Hesperiidae)

Abstract: Abstract. There are isolated populations of the endangered butterfly, Pyrgus sidae, on the Iberian Peninsula. The mark-releaserecapture method was used to study the population parameters, the use of resources and the spatial distribution of a population in the centre of Spain. The estimated number of males and females within the population were similar and did not differ significantly from a ratio of 1 : 1. Total population size was estimated to be 569 ± 83 individuals. Potentilla recta is the principal adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
(22 reference statements)
1
4
0
Order By: Relevance
“…The females layed eggs on fresh leaves of the larval foodplants in all cases, with the exception of P. cinarae (Rambur), which used the fruits (head of achenes of Potentilla recta and P. hirta or the polyachenes of Filipendula vulgaris) and P. sidae, which laid eggs on the flowers. These exceptions are congruent with the ecological specialization of both species (Nel 1984, Hernández-Roldán et al 2009, Hernández-Roldán et al 20092011a).…”
Section: Foodplantssupporting
confidence: 76%
See 1 more Smart Citation
“…The females layed eggs on fresh leaves of the larval foodplants in all cases, with the exception of P. cinarae (Rambur), which used the fruits (head of achenes of Potentilla recta and P. hirta or the polyachenes of Filipendula vulgaris) and P. sidae, which laid eggs on the flowers. These exceptions are congruent with the ecological specialization of both species (Nel 1984, Hernández-Roldán et al 2009, Hernández-Roldán et al 20092011a).…”
Section: Foodplantssupporting
confidence: 76%
“…Larvae of all species feed on the leaves and again the exception is P. sidae, which feeds on the flowers and stipules of the plant during the first instars and after that also feeds on the leaves (Hernández-Roldán et al 2009). All species build larval shelters by joining leaves with silk threads.…”
Section: Foodplantsmentioning
confidence: 99%
“…Being restricted to habitats not strongly affected by climatic oscillations could be the product of an unusually limited dispersal capability, which would account for the inability to have expanded during interglacial periods, producing a long‐term disjunct distribution. If this hypothesis is correct, the predicted dispersal capability of P. cinarae should be substantially lower than that of P. sidae , which is difficult to imagine because a capture–mark–recapture study on Iberian P. sidae showed that this is already a typical sedentary species with low dispersal capabilities (Hernández‐Roldán et al. , 2009).…”
Section: Discussionmentioning
confidence: 99%
“…We reported the mode and 95% highest posterior densities (HPD) for each parameter (2,000,000 Markov chain interactions; burn‐in = 500,000; M = 0; T max = 5; θ = auto‐initialize). In the absence of a specific mutation rate for Pyrgus , we assumed a generation time of 1 year based on the evidence that these species are univoltine (Hernández‐Roldán et al. , 2009; Wagner, 2009), and a 1.5% Myr −1 divergence rate for arthropod COI (Quek et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation